PENTINGNYA PENGETAHUAN PAJAK UNTUK MENINGKATKAN KEPATUHAN PAJAK UMKM (STUDI KASUS UD SUMBER AYU) - Huwaidah Nabila; Agustine Dwianika (Universitas Kristen Krida Wacana, 2020)
Income tax revenue in the MSME sector has a potential to has a large increasing percentage due to the increasing number of MSMEs currently the government made an effort with issuing a special tax rate for MSMEs listed in Government Regulation No.46 of 2013 with income tax rate at 1% which is currently changed into Government Regulation No.23 of 2018 with a reduced rate to 0,5%. The purpose of this journal is to provide tax knowledge in general to MSMEs in an effort to improve tax compliance of MSME. The researcher conducted a case study on one of the MSMEs, namely Sumber Ayu. This paper uses two types of dara, that is primary data in the form of direct interview with respondent who meet the criterian and secondary data in the form of report on recording gross income (turnover) which is obtained directly from respondent who meet the criteria. The result of this paper is Sumber Ayu didn’t calculate, pay and report income tax due to its lack of tax knowledge. Keywords: MSME, tax knowledge, tax compliance